Pengaruh Lingkungan Berbahasa Arab dan Interaksi Sosial terhadap Kemampuan Menulis Bahasa Arab di Lembaga Studi Bahasa Asing Asrama Jalaluddin Ar-Rumi - M. Naufal Al Qurthuby Fuady S.; Munirul Abidin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Writing proficiency in Arabic is a complex productive skill that requires mastery of vocabulary, sentence structure, and appropriate language use within context. In foreign language learning institutions such as the Jalaluddin Ar-Rumi Dormitory, the writing process is often influenced by external factors, including the Arabic-speaking environment and social interaction among students. This study aims to analyze the extent to which these two factors affect students' Arabic writing skills. A quantitative approach with a correlational survey design was used. The sample consisted of 40 purposively selected students. Data were collected through a closed-ended questionnaire to measure the Arabic-speaking environment and social interaction, as well as a writing test to assess writing ability. Data were analyzed using multiple linear regression. The results showed that both the Arabic-speaking environment and social interaction had a positive and significant effect on writing skills, with the Arabic-speaking environment having a more dominant influence. These findings highlight the importance of creating a learning atmosphere that actively and interactively supports the use of Arabic. The implications of this study point to the need for strengthening language immersion strategies and structured social interaction programs as integral components in developing Arabic writing proficiency in language institutions.